Historical Assessment of Floral and Faun al Representation of Ancient Indian Sculpture - Lama, Sudas; Choudhury, Anamika (University of North Bengal, 2017)
The Sculptural art of India occupies the foremost place in the history of world art. The artist in India had attained a high degree of excellence at a very early period and specimens produced by him are truly marvels of human industry and skill. One finds in them an intensity of feeling, a revelation of the powers of the unseen which is not approached in the art elsewhere in the world. The success of artistic production depends on the intensity of the artist 's realization of his beauty and his ability to interpret his experience to others.
Karatoya : North Bengal University journal of History, Vol. 10, March-2017, pp. 82-94
Keywords: Sculpture; Animal figures; Maurya; Rhythm; Flora; Fauna